"Sustainable development in water and sanitation" : a case study of the water and sanitation system at the Lynedoch Ecovillage Development - Dowling, T. J. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (School of Public Management and Planning))--University of Stellenbosch, 2007.